Impact of Depth and Hydraulic Retention Time on Surfactant Removal in High-Rate Algal Pond - Farias, Sarah Lacerda; Ruas, Graziele [UNESP]; Silva, Josiane Aparecida Rodrigues; Stral, Samara; Serejo, Mayara Leite; Boncz, Marc Árpád [UNESP] (Springer Nature, 2025)
Surfactants, which are emerging pollutants found in detergents, fabric softeners, and other products, pose a significant challenge in wastewater treatment. These compounds are persistent under anaerobic conditions and can harm the biological treatment process, despite being biodegradable in aerobic environments. In this study, we assessed the performance enhancement of the microalgae-bacteria system implemented in a high rate algal pond (HRAP)—a cost-effective wastewater treatment technology known for its proven efficiency in removing persistent pollutants, including surfactants. For this purpose, the height of the water depth and the hydraulic retention time (HRT) were investigated. Three HRAPs reactors were used: R1 with a volume of 70 L, 25 cm of water depth and HRT of 2 days, and R2 and R3 with a volume of 40 L, 15 cm of height and HRT of 2 and 5 days, respectively. A microalgae culture with 0.95 g L−1 of total suspended solids (TSS), and nitrifying-denitrifying activated sludge from a sewage treatment plant (WWTP), with 0.9 gTSS L−1 were used as inocula. The experiment lasted 40 days, installed in outdoor condition with a temperature ≈20.5 °C. In the three conditions studied, surfactant removals were expressive but without significant difference between them (p < 0.05), with means of 89 ± 8, 93 ± 5, and 93 ± 4% for R1, R2 and R3, respectively. However, for biomass growth, the lower water depth and a 5-day HRT allowed averages of 0.6 gTSS L−1, while for R1 and R2 the growth was similar with 0.3 gTSS L−1. These results demonstrate the potential of HRAPs for treating effluents containing surfactants. Among the tested conditions of water depth and HRT, other factors must be considered such as nutrient removal efficiency, organic matter, algal biomass sedimentability, analysis of energy consumption, thus providing an efficient and economical operation of HRAPs.